2020
DOI: 10.1155/2020/8831172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Etiology, and Risk Factors of Mastitis in Dairy Cattle in Embu and Kajiado Counties, Kenya

Abstract: Bovine mastitis continues to be a leading cause of heavy economic losses in the dairy industry and a public health hazard globally. This cross-sectional study investigated the prevalence, etiologies of clinical and subclinical mastitis, and associated predisposing factors in Embu and Kajiado counties in Kenya. A semistructured questionnaire was administered to 154 smallholder dairy farmers to collect data on management practices, animal factors, and disease history. A total of 395 dairy cows were initially scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
36
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 48 publications
16
36
7
Order By: Relevance
“…The clinical manifestations of MG inflammation as well as its further course depend on the interplay between the innate resistance and adaptive immunity of the dairy cow and the type, concentration, and virulence of udder pathogens. If the MG has been infected with a large number of pathogens or more germs that are virulent and the host's defense systems have not been sufficient to control the infection, an clinical or chronic form of mastitis will develop ( 22 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations of MG inflammation as well as its further course depend on the interplay between the innate resistance and adaptive immunity of the dairy cow and the type, concentration, and virulence of udder pathogens. If the MG has been infected with a large number of pathogens or more germs that are virulent and the host's defense systems have not been sufficient to control the infection, an clinical or chronic form of mastitis will develop ( 22 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…aureus, E. coli with Klebsiella. However, the maximum loss of production in multiparous is caused by Streptococcus spp., Staphylococcus aureus and others pathogens [46,47]. The loss of production is higher in multiparous cows than primiparous.…”
Section: Low Milk Yieldmentioning
confidence: 99%
“…Globally, mastitis is an inflammation of the mammary gland, affecting dairy cows with high economic impact, including low milk production, increasing antibiotic residue contamination, and chronic infection, often leading to deaths [1,2]. It was reported that the prevalence of subclinical mastitis is higher than that of clinical mastitis [3]. Subclinical mastitis has a more common and serious impact on older lactating animals, contributing to most of the financial losses [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical mastitis has a more common and serious impact on older lactating animals, contributing to most of the financial losses [2,4]. The major risk factors for developing mastitis include herd size, bedding material, and milking of mastitic cows [1,3]. Meanwhile, the age and number of parity (number of pregnancies carried by a cow) were significantly associated with the occurrence of subclinical mastitis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation